Critics' Thoughts on the Development of Arabic Literature Criticism in the Umayyad Era - Aprianti, Jashinta; Tasnimah, Tatik Mariyatut (Universitas Muhammadiyah Gorontalo, 2024)
This research aims to review literary criticism during the Umayyad period and look at who the critics were during the Umayyad period. As explained regarding Arabic literary criticism in the Hijaz, Iraq and Sham regions. The Umayyad dynasty was named after Umayyah bin Shams, one of the leaders of the Quraysh tribe known as Banu Umayyah. in this research is a descriptive qualitative method, by describing how the influence of the critic's perspective on the development of Arabic literary criticism in the Umayyad era. The results of the research of famous critics in the Hijaz region are Ibn Abi Atieq and Sukainah bint al Husein. Ibn Abi Atieq's Criticism Criteria: Good poetry is poetry whose meaning is subtle, good introduction, easy to pronounce, easy to understand, and easy to express. While Sukainah Binti Al Hussein bin Abi Talib criticized the literary works of poetry, one of which examined the text of the poem and examined the image of women painted by the poet. In the Iraq region, the comparison between al Akhtal, Jarir and al Farazdaq, that Jarir took from the sea, al Farazdaq carved from stone. While the most important Levant is Madh (praise). In the Levant the famous critics of the Levant are Kusair Azza and al Akhtal. Criticism came in the form of formal criticism and artistic criticism.